The Influence of Co-Creation Activities, Co-Creation Values ​​and Trust on Satisfaction and Loyalty at Indonesian Islamic Universities - B, Idwal; Fadli, Fadli; Faisal Muttaqin, (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Marketing literature is still limited to studies conducted on Islamic higher education services. There is still a gap in research that tests Service Dominant logic on marketing performance in Islamic higher education. This study empirically tests the influence of student co-creation activities, student co-creation values, and trust in lecturers, their influence on student satisfaction with lecturers, and their impact on loyalty to the study program. Data collection in the field was carried out in the Islamic Higher Education Management Study Program in Indonesia, namely Bengkulu, Lampung, and Bogor. The next stage is the data processing stage using Structural Equation Model Analysis (SEM) to obtain answers to research questions. The results found that student co-creation activities - in the form of providing feedback, getting information, helping and carrying out obligations - have a positive effect on student satisfaction with lecturers, and then this satisfaction has a positive effect on student loyalty. Student co-creation values ​​and trust partially mediate the relationship between student co-creation activities and satisfaction with lecturers in the context of higher education services. With these results, it means that the influence of co-creation activities carried out by students in their daily lives can directly affect student satisfaction with lecturers, or can indirectly affect students through the role of co-creation values ​​obtained by students and student trust in lecturers.